Predictors of Functional Dependence After COVID-19: A Retrospective Examination Among Veterans. (January 2021) - Leigh, Alexandra E.; McCall, Jonathan; Burke, Rebecca V.; Rome, Robin; Raines, Amanda M.
Abstract : Objective: The aim of this study was to examine the impact of demographics, preexisting medical conditions, and in-hospital complications of COVID-19 infection on functional status at discharge. Design and Participants: A retrospective chart review was conducted on 119 patients hospitalized for COVID-19 infection between March 1, 2020, and April 20, 2020. Demographics, preexisting medical conditions, and newly diagnosed COVID-19 complications were collected from electronic medical records and entered in a deidentified database. Main Outcome: The primary outcome was functional status at discharge, as measured by independence in activities of daily living. Results: Older age, respiratory failure, cardiac conditions, and thromboembolic complications all made a statistically significant contribution to functional dependence at discharge, with thromboembolic complications evincing the strongest association (odds ratio, 25.58). Conclusion and Relevance: New diagnosis of thrombosis during COVID-19 hospitalization, a measure of COVID-19 disease severity, was the factor most associated with dependence in activities of daily living at discharge. Interestingly, preexisting conditions including hypertension, severe obesity, lung disease, and diabetes did not correlate with dependent functional status at discharge. Abstract : Supplemental digital content is available in the text.